ANALISIS STRATEGI PENGEMBANGAN SUMBER DAYA MANUSIA APARATUR PEMERINTAH KOTA MATARAM DALAM MEWUJUDKAN KOTA MATARAM SEBAGAI KOTA LAYAK ANAK - Erni Suryani (Master of Management, Mataram University, 2017)
The strategy of human resource development is an activity that should be conducted to optimize the performance of government apparatus of Mataram to make the city as children-feasible city. This research is aimed at (1) analyzing the issue of strategy of human resource development to make Mataram as children-feasible city, (2) formulizing the strategy of human resource development to make Mataram as children-feasible city. This research is descriptive qualitative research within the quantitative approach. The qualitative and quantitative data were collected through in-depth interview, observation, and documentation. The informants of this study are the stakeholders and the KLA holding institution of 10 SKPD in Mataram. the data then were analyzed using Force Field Analysis. The validity of data were examined with triangulation technique. The research identified that human resources of Mataram city are not available yet for children right convention. The strategy of human resource development is recommended to use functional human resource development strategy through organizational development and training for apparatus. The researcher then using need analysis identified the gap between competence and apparatus performance standard for KLA staff.Keywords: human resource development strategy, functional development strategy, children-feasible city